Venice at 60: Article 5 and the acceptable limits of use - Nigel Walter (Ochrona Dziedzictwa Kulturowego)
The Venice Charter is central to modern conservation, and foundational for ICOMOS specifically; yet its contemporary relevance is debatable. These and other issues were discussed by ICOMOS in Budapest 20 years ago, in a conference marking the Charter’s 40th anniversary. However, questions remain as to its ongoing significance. As Bogusław Szmygin asked in 2004, does the Charter remain the ‘Decalogue' of the conservation discipline, or has it itself become a ‘Historical Monument’?The Venice Charter as a product of high modernity, with its belief in a definitive break with the past and an overcoming of tradition. The paper assesses the Charter’s ongoing relevance in relation to one pressing issue in contemporary conservation, the limits to the acceptable use of – and change to – historic buildings (Art. 5), and using an example of recent change to an English parish church. The paper argues that the acknowledged need for the interpretation of the Charter requires a hermeneutically literate approach which acknowledges the limits of a scientific/technical reading of any historic monument – the Charter included – and the importance of a dynamic understanding of the living tradition that is conservation. It concludes that the Charter remains a central text for the conservation discipline, which itself is a tradition in good health, and for that very reason its status will continue to be fiercely debated.